Development of mRNA vaccines against respiratory syncytial virus (RSV). (December 2022) - Qiu, Xirui; Xu, Siyan; Lu, Yang; Luo, Zichen; Yan, Yangtian; Wang, Chuyue; Ji, Jianjian
Abstract: Respiratory syncytial virus (RSV) is a single-stranded negative-sense RNA virus that is the primary etiologic pathogen of bronchitis and pneumonia in infants and the elderly. Currently, no preventative vaccine has been approved for RSV infection. However, advances in the characterization, and structural resolution, of the RSV surface fusion glycoprotein have revolutionized RSV vaccine development by providing a new target for preventive interventions. In general, six different approaches have been adopted in the development of preventative RSV therapeutics, namely, particle-based vaccines, vector-based vaccines, live-attenuated or chimeric vaccines, subunit vaccines, mRNA vaccines, and monoclonal antibodies. Among these preventive interventions, MVA-BN-RSV, RSVpreF3, RSVpreF, Ad26. RSV.preF, nirsevimab, clesrovimab and mRNA-1345 is being tested in phase 3 clinical trials, and displays the most promising in infant or elderly populations. Accompanied by the huge success of mRNA vaccines in COVID-19, mRNA vaccines have been rapidly developed, with many having entered clinical studies, in which they have demonstrated encouraging results and acceptable safety profiles. In fact, Moderna has received FDA approval, granting fast-track designation for an investigational single-dose mRNA-1345 vaccine against RSV in adults over 60 years of age. Hence, mRNA vaccines may represent a new, more successful, chapter in the continued battle to develop effective preventative measures against RSV. This review discusses the structure, life cycle, and brief history of RSV, while also presenting the current advancements in RSV preventatives, with a focus on the latest progress in RSV mRNA vaccine development. Finally, future prospects for this field are presented. Graphical Abstract: ga1 Highlights: RSV is the primary etiologic pathogen of bronchitis and pneumonia in infants and the elderly. The in-depth understanding of RSV fusion protein provides a new target for preventive interventions. The brief history and current status of six approaches to prevent RSV infection were reviewed. RSV mRNA vaccines are promising candidates due to rapid development, safety, and effectiveness.